Temptation in the Archives : Essays in Golden Age Dutch Culture - Jardine, Lisa (Book collections on Project MUSE., 2015)
Through the study of such key figures as Sir Constantjin Huygens, a Dutch polymath and diplomat, we begin to see the Anglo-Dutch cultural connections that formed during this period against the backdrop of unfolding political events in England. Temptation in the Archives paints a picture of a unique relationship between the Netherlands and England in the 17th century forged through a shared experience - and reveals the lessons we can learn from it today.